Task-dependent modulation of corticospinal excitability and inhibition following strength training. (June 2020) - Siddique, Ummatul; Rahman, Simin; Frazer, Ashlyn; Leung, Michael; Pearce, Alan J.; Kidgell, Dawson J.
Abstract: This study determined whether there are task-dependent differences in cortical excitability following different types of strength training. Transcranial magnetic stimulation (TMS) measured corticospinal excitability (CSE) and intracortical inhibition (ICI) of the biceps brachii muscle in 42 healthy subjects that were randomised to either paced-strength-training (PST, n  = 11), self-paced strength-training (SPST, n  = 11), isometric strength-training (IST, n  = 10) or to a control group ( n  = 10). Single-pulse and paired-pulse TMS were applied prior to and following 4-weeks of strength-training. PST increased CSE compared to SPST, IST and the control group (all P  < 0.05). ICI was only reduced (60%) following PST. Dynamic strength increased by 18 and 25% following PST and SPST, whilst isometric strength increased by 20% following IST. There were no associations between the behavioural outcome measures and the change in CSE and ICI. The corticospinal responses to strength-training are task-dependent, which is a new finding. Strength-training that is performed slowly could promote use-dependent plasticity in populations with reduced volitional drive, such as during periods of limb immobilization, musculoskeletal injury or stroke.